Perfil laboral y educativo de los niños en México, 1984-2000 - Robles-Vásquez, Héctor; Abler, Dave (Papeles de Población, 2021)
The year 2000 was a turning point for child labor in Mexico. In rural areas, labor force participation by male and female children aged 12 to 14 years and females aged 15 to 17 years decreased. At the same time, there was an increase in the percentage of students not participating in fue labor force. Progresa appears to be fue cause oflower labor force participation rates among rural children. However, it did not have success in increasing school attendance among adolescents in fue labor force or those working in the home. This study finds that children's economic activity is associated with their education. On average, only children aged 12-14 who are attending school and not working complete their basic education on time. Data for fue study are from the Mexican Household Income & Expenditures surveys from 1984 to 2000.